ANALISIS MUTU LAYANAN DITINJAU DARI PROGRAM STUDI, GENDER, ANGKATAN, DAN PRESTASI AKADEMIK - Bayu Budi Prakoso; Sasminta Christina Yuli Hartati; Achmad Rizanul Wahyudi (UHN IGB Sugriwa Denpasar, 2023)
The level of faculty service to students is important to know as the basis for evaluating the quality of education implementation. Management services, finance, and infrastructure are the main aspects of educational services at the sports science faculty because the educational process tends to use more sports facilities and infrastructure. This article aims to describe the results of a survey on the level of faculty service to prospective students for sports personnel. This survey research was conducted on 325 students (male = 222, female = 103; Class of 2019 = 44, 2020 = 132, 2021 = 149). Instruments for the level of student satisfaction with management services, finance, and infrastructure have been standardized by quality assurance used in research. Data analysis used CFA, Mann-Whitney (gender), Kruskal-Wallis (study program and batch), correlation, and Wilcoxon. The results showed that the instrument for measuring student satisfaction had met the validity and reliability requirements. There is no difference in the level of faculty service in terms of gender, study program, and year of student entry (class). In addition, the cumulative achievement index does not correlate with the gap in services provided by the faculty. The gap between expectations and reality of 0.24 is included in the positive category (more satisfied than expectations) with a value of Z = -8.389, p = 0.000. So it was concluded that student satisfaction was declared positive and not influenced by differences in student characteristics and GPA